Prevalence of hepatitis E virus in swine in China: a systematic review with meta-analysis (2004–2023) - He, Zhenwen; Liu, Dingyu; Liu, Baoling; Zhang, Pian; Wang, Xiaohu; Wang, Gang; Huang, Yuan; Chen, Jing; Cai, Rujian (Frontiers in Veterinary Science, 2025)
IntroductionHepatitis E virus (HEV) is a major cause of acute hepatitis in humans and recognized as a zoonotic pathogen, with swine serving as a primary reservoir. Despite substantial research, comprehensive analysis encompassing regional variations and pig growth stages within China, as well as the influence of recent biosecurity measures on HEV prevalence, remains limited. In this study, we aim to assess the prevalence and risk factors associated with swine HEV in China.MethodsA thorough review of HEV infection studies was conducted using six databases: China National Knowledge Infrastructure, Wanfang, Wipro, Centre for Agriculture and Biosciences International, PubMed, and ScienceDirect, covering publications from January 1, 2004 to December 31, 2023. Eighty-seven studies investigating the seroprevalence of swine HEV IgG antibodies and HEV RNA detection rates were included. A rigorous meta-analysis and quality assessment followed.ResultsThe combined seroprevalence of swine HEV IgG antibodies was 58.0% (95% confidence interval [CI]: 52.0–65.0). The seroprevalence from 2019 to 2023 was lower (27.4, 95% CI: 26.3–28.2) than that in other years. The seroprevalence was higher in sows (67.2, 95% CI: 55.8–78.7) than in suckling, nursery, and fattening pigs. The detection rate of HEV RNA was 13.0% (95% CI: 11.0–15.0), with fattening pigs showing a significantly higher positivity rate (16.9, 95% CI: 13.2–20.7) than sows and suckling pigs. HEV RNA detection was significantly lower in bile (8.3, 95% CI: 6.3–10.3) than in feces and liver.DiscussionThis study highlights the widespread presence of HEV in pig farms across China, with prevalence strongly linked to pig growth stage, study year, and sample type. The findings underscore the importance of pig growth stage, sample type, and recent biosecurity measures in controlling HEV prevalence, providing actionable insights for improving biosecurity practices in pig farms.